PENGARUH TINGKAT PENDIDIKAN DAN INVESTASI TERHADAP TINGKAT PENGANGGURAN DI PROVINSI RIAU - Saragih Marcallino Joshua; Harlen Harlen; Indrawati Toti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of the level of education and investment on the unemployment rate in Riau Province. The type of data used is secondary data, the method of collecting data is the method of documentation. The data used is time series data for the 2006-2019 period. The analytical method used is multiple linear regression. The results of this study are the level of education and investment simultaneously affect the level of increasing unemployment. Partially the level of education has a negative and insignificant effect on the unemployment rate and investment has a negative and significant effect on the unemployment rate.Keyword : Level od education, Investment, unemployment rate